Prevalence and Risk Factors of Self-Medication Among the Pediatric Population in China: A National Survey - Yuan, Jing; Du, Wandi; Li, Zhiping; Deng, Qiao; Ma, Guo (Frontiers in Public Health, 2022)
Background Self-medication of antibiotics is common in China, whereas the self-medication of other medicines is still unknown, especially for the younger children who are vulnerable to adverse drug events. The aim of this study was to estimate the prevalence of self-medication reported by parents among children under age 12 in China. Methods A national cross-sectional survey was conducted among parents of children under age 12 in China by using a self-administered online questionnaire. Parents were asked whether they have self-medicated their children in the past 12 months. Logistic regression analysis was performed to access the risk factors of self-medication. Results Eligible questionnaires were obtained from 4,608 parents. The majority of respondents were mothers aged between 30 and 39 years old who held a college degree. A total of 1,116 (or 24.21%) respondents reported self-medication in the previous year. In the logistic regression model, parents with graduate degrees were less likely to self-medicate their children [Adjusted OR (AOR) = 0.436; 95% CI = 0.296–0.641]. The odds of self-medication were associated with being a father, living in Northern China, having a child at age 6–11, even though these did not reach statistical significance. Conclusions Our findings indicate that self-medication are common in children under age 12, highlighting the drug safety issue in China. It seems that the educational level is the risk factors of self-medication. More targeted intervention and educational program should be implemented to improve drug safety.